Advances in the Pharmacological Management of Diabetic Nephropathy: A 2022 International Update - Rosaria Vincenza Giglio; Angelo Maria Patti; Ali Abbas Rizvi; Anca Panta Stoian; Marcello Ciaccio; Nikolaos Papanas; Andrej Janez; Alper Sonmez; Maciej Banach; Amirhossein Sahebkar; Manfredi Rizzo (Biomedicines, 2023)
Diabetic nephropathy (DN) is the leading cause of end-stage renal disease (ESRD) worldwide. Its pathogenesis encompasses functional alterations involving elevated intraglomerular and systemic pressure, increased activity of the renin-angiotensin system (RAS) and oxidative stress, and the eventual development of renal fibrosis. The management of DN involves the optimization of blood pressure (BP) and blood glucose targets. However, treatment of these risk factors slows down but does not stop the progression of DN. Innovative pharmacologic therapies for dyslipidemia and type 2 diabetes mellitus (T2DM) could play a key role in bridging this gap and attenuating the residual risk of DN beyond traditional risk factor management. Glucagon-like peptide-1 receptor agonists (GLP-1 RAs), sodium-glucose cotransporter-2 inhibitors (SGLT-2is), and inhibitors of mineralocorticoid receptor-mediated sodium reabsorption are recently introduced drug classes that have been shown to have positive effects on kidney function in individuals with T2DM. The aim of this review is to provide an update on the therapeutic options available in order to prevent or slow the onset and progression of DN in diabetic patients.